Saber local e educação musical: vozes de cantoras compositoras afrodescendentes do Maranhão - COSTA, Fernanda Silva da (2024)
The present study examines, in the narratives of Afro-Maranhão composers Dona Teté do Cacuriá (1924-2011), Patativa (1937), and Célia Sampaio (1964), possibilities of incorporating the musical knowledge originating from the musical production of the three singers/composers into the educational practices of teachers from elementary to higher education, including post-graduation. Specifically, this research investigates studies on musical practices of composers in Brazil; identifies in the legal documents that govern Brazilian Education the guidelines and norms dealing with topics such as local knowledge and Afrocentricity in schools; and it follows the trajectory of Afro-descendant women who have acted/act in Maranhão's musical production, highlighting, through narratives, the musical knowledge stemming from their musical productions and their relationship with the teaching of Afro-Brazilian music. It arises from the need to disseminate local knowledge produced by Afro-Maranhão women in school spaces because even with historical advancements regarding the female figure in the artistic field, studies like Nochlin's (2016) show that women's participation in art was scarce, and the rare women who produced the "great art," for example, were not sufficiently investigated over time. Therefore, it is worth reflecting: if producers of "great art" were little investigated, Afro-descendant popular artists were even less so. It has a qualitative methodological basis and uses narrative interviews, literature review, and documentary analysis as data production and analysis techniques. It dialogues with authors such as Lélia Gonzalez (2020), Walter Mignolo (2017), Bernardino-Costa (2016), Aníbal Quijano (2005), among others, who deal with decolonial epistemology; Queiroz (2020), Sousa (2021), and Batista (2018) on relations between music and the decolonial perspective, and Asante (2009; 2016) regarding the concept of Afrocentricity. The results show that studies on composers are still underdeveloped in Brazil and that existing research rarely makes a direct connection with the field of education and with the ethnic-racial perspective. The data also show that Higher Education and Basic Education should open up greater spaces for musical practices that value cultural plurality aiming at an anti-racist and decolonial education. Finally, the results indicate that women like Dona Teté do Cacuriá (1924-2011), Patativa (1937), and Célia Sampaio (1964), through music, express knowledge of local culture influenced by African culture and, through their compositions, contribute to shaping the cultural identity of the Maranhão people and the artistic diversity of the state, whose knowledge needs to be incorporated into the schooling processes from elementary to higher education.